Single‐core soft‐switching high step‐up three‐level boost converter with active clamp. Issue 14 (1st November 2016) - Poorali, Behzad; Moradmand Jazi, Hamed; Adib, Ehsan
Abstract : In this study, a new three‐level boost converter is introduced which has high voltage gains suitable for photovoltaic applications. Three‐level structure has the advantage of low voltage stresses of the switches and diodes. In the proposed converter, semiconductor devices operate under soft‐switching conditions which results in low switching losses. It utilises an active clamp circuit with one auxiliary switch to absorb the leakage energy. Therefore, elimination of the voltage spikes across the switches as well as efficiency improvement is achieved. On the other hand, the proposed converter has one magnetic core, and consequently, reduced size. Operating principles of the proposed converter along with its theoretical analysis are presented. Experimental results of a 200 W laboratory prototype for voltage conversion of 40 V/400 V are provided in order to verify the proposed converter performance.